Genome-wide identification and bioinformatics analysis of the WRKY transcription factors and screening of candidate genes for anthocyanin biosynthesis in azalea (Rhododendron simsii) - Wang, Cheng; Ye, Dan; Li, Yan; Hu, Peiling; Xu, Run; Wang, Xiaojing (Frontiers in Genetics, 2023)
Plant anthocyanins are secondary metabolites that are mostly in charge of the red, pink, blue, and purple hues observed in fruits and flowers. WRKY transcription factors have been demonstrated to influence the anthocyanin biosynthesis in many plant species. There is limited knowledge about the structure and function of WRKY genes in the major ornamental plant azalea (Rhododendron simsii). In this study, 57 RsWRKY genes from the genome of R. simsii were discovered and compared to genes from 22 other typical plants. The 57 RsWRKYs were divided into three main groups and several subgroups based on their structural and phylogenetic characteristics. Gene duplication analysis indicated that the expansion of the RsWRKY gene family was primarily due to WGD duplication. In addition, RNA-seq data was used to examine the expression patterns of RsWRKYs. Further investigation revealed that 17 candidate genes were associated with anthocyanin synthesis at the bud stage while 9 candidate genes were linked to anthocyanin synthesis at the full bloom stage. These findings will act as a starting point for future functional WRKY gene studies and investigations into the molecular mechanisms behind anthocyanin biosynthesis in Rhododendron species.